2018
DOI: 10.2196/cancer.7952
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Media in the Assessment of Relative Effectiveness: Explorative Review With Examples From Oncology

Abstract: BackgroundAn element of health technology assessment constitutes assessing the clinical effectiveness of drugs, generally called relative effectiveness assessment. Little real-world evidence is available directly after market access, therefore randomized controlled trials are used to obtain information for relative effectiveness assessment. However, there is growing interest in using real-world data for relative effectiveness assessment. Social media may provide a source of real-world data.ObjectiveWe assessed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…On the other hand, not all patients will have access to the internet [ 36 , 40 ], the population of patients using the internet may not reflect all patients [ 16 , 18 , 20 – 22 ], information bias may occur (e.g. duplication of social media messages or multiple messages from the same patient) [ 16 19 ], interpreting messages posted by patients may prove to be difficult for researchers, and it may be difficult to validate the authenticity of respondents via social media [ 16 ]. Keeping these disadvantages in mind, it should be emphasized that data collected through social media should be used complementary to traditional methods or provide insights where no data is otherwise available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, not all patients will have access to the internet [ 36 , 40 ], the population of patients using the internet may not reflect all patients [ 16 , 18 , 20 – 22 ], information bias may occur (e.g. duplication of social media messages or multiple messages from the same patient) [ 16 19 ], interpreting messages posted by patients may prove to be difficult for researchers, and it may be difficult to validate the authenticity of respondents via social media [ 16 ]. Keeping these disadvantages in mind, it should be emphasized that data collected through social media should be used complementary to traditional methods or provide insights where no data is otherwise available.…”
Section: Discussionmentioning
confidence: 99%
“…The IMI-GetReal initiative is a 3-year public-private partnership exploring the use of Real-World Evidence (RWE) in early drug development and drug assessment [ 15 ], including a series of case studies. Here presented is our case study on metastatic melanoma where the potential of social media as a new source of RWE for HTA was investigated within a pilot literature review [ 12 , 16 ]. This research demonstrated the potential value of using social media to inform several parameters of HTA in oncology, including: adverse events [ 12 , 17 19 ], treatment adherence [ 18 ] and HRQoL [ 12 , 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aware of the shortfalls of EBM's strict hierarchy, the Institute now makes use of, for example, GRADE (see Guyatt et al, 2008), an EBM-method that allows more flexibility within the original hierarchy. The Institute is also exploring how to use 'realworld data' (Makady et al, 2017) and patient experiences from social media in health technology assessments (Kalf et al, 2018). This "repair and maintenance work" shows that policymakers continue to search for ways to meaningfully combine patients' and professionals' embodied, qualitative knowledge with aggregate, quantitative knowledge in policymaking.…”
Section: Discussionmentioning
confidence: 99%
“…Effective ways to include patients' knowledge in public decision-making are still being developed and researched (e.g. Lavis et al, 2009), also by the Institute (Kalf et al, 2018;Makady et al, 2017).…”
Section: Testimonial (In)justicementioning
confidence: 99%
“…Similar to approaches analyzing the effectiveness of other behavioral or pharmacological interventions, this method could be used as a low-cost means of patient monitoring. This is especially valuable among youth and adolescent populations, who tend to display less compliance with ecological momentary assessment reporting [36,37].…”
Section: Discussionmentioning
confidence: 99%